2017
DOI: 10.1371/journal.pone.0171416
|View full text |Cite
|
Sign up to set email alerts
|

No neuronal loss, but alterations of the GDNF system in asymptomatic diverticulosis

Abstract: BackgroundGlial cell line-derived neurotrophic factor (GDNF) is a potent neurotrophic factor known to promote the survival and maintenance of neurons not only in the developing but also in the adult enteric nervous system. As diverticular disease (DD) is associated with reduced myenteric neurons, alterations of the GDNF system were studied in asymptomatic diverticulosis (diverticulosis) and DD.MethodsMorphometric analysis for quantifying myenteric ganglia and neurons were assessed in colonic full-thickness sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
(48 reference statements)
1
20
0
2
Order By: Relevance
“…investigated by Böttner et al (2013), who observed decreased gene expression levels of the receptors for GDNF, RET, and GFRα1. A refined analysis revealed that the down-regulation of both receptors was most pronounced in myenteric ganglia (Barrenschee et al, 2017), thereby resembling the actual data on the NRG1-ErbB2/ErbB3 system in DD: The ErbB3 receptor predominantly expressed in enteric neuronal tissue is diminished in DD, whereas the ErbB2 receptor primarily expressed by enteric smooth muscle cells (Barrenschee et al, 2015) is not affected.…”
Section: Neurotrophic Factors and Their Corresponding Receptors In Ddsupporting
confidence: 66%
See 3 more Smart Citations
“…investigated by Böttner et al (2013), who observed decreased gene expression levels of the receptors for GDNF, RET, and GFRα1. A refined analysis revealed that the down-regulation of both receptors was most pronounced in myenteric ganglia (Barrenschee et al, 2017), thereby resembling the actual data on the NRG1-ErbB2/ErbB3 system in DD: The ErbB3 receptor predominantly expressed in enteric neuronal tissue is diminished in DD, whereas the ErbB2 receptor primarily expressed by enteric smooth muscle cells (Barrenschee et al, 2015) is not affected.…”
Section: Neurotrophic Factors and Their Corresponding Receptors In Ddsupporting
confidence: 66%
“…Image acquisition, processing, and analysis were performed as previously described (Barrenschee et al, 2017). Briefly, fluorescence immunohistochemical signals of myenteric ganglia (n = 8) were recorded in specimens of controls and patients with DD.…”
Section: Quantitation Of Immunofluorescence Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in glial cell line-derived neurotrophic factor ( GDNF ) have been suggested to act in concert with RET mutations to produce aganglionic megacolon (Hirschsprung’s disease), which is characterised by congenital absence of intrinsic ganglion cells in the myenteric and submucosal plexuses of the GI tract 30. Impaired GDNF function has been shown at gene and protein level to occur in diverticular disease and during early stages of diverticula formation 31. Plausible links to neuronal physiology are also evident for GPR158 , a G-protein coupled orphan receptor32 and brain-derived neurotropic factor.…”
Section: Discussionmentioning
confidence: 99%